Liver Dysfunction as a Novel Player in Alzheimer’s Progression: Looking Outside the Brain - Estrada, Lisbell D.; Ahumada, Pablo; Cabrera, Daniel; Arab, Juan P. (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD), which afflicts an estimated 20 million people worldwide, is the most common cause of dementia in the elderly and constitutes the fourth leading cause of death in the developed world. The major neuropathological features of AD are synaptic and neuronal degeneration and the presence of amyloid plaques and neurofibrillary tangles. The main protein component of the amyloid plaques is the amyloid-beta peptide (Aβ). Accumulation of Aβ in the brain of AD patients is thought to be central in the pathogenesis of AD. During the last decade, it has become been clear that the synaptic loss and neuronal degeneration underlying early cognitive impairments are caused by small aggregates termed Aβ oligomers. The blood brain barrier (BBB) is a layer of tightly packed cells that normally regulates the entry of substances into the brain, whiles maintains the removal of toxic molecules from brain to blood. Alzheimer ́s patients and research models evidence BBB impairment and dysfunction accompanying AD. It is not clearly understood if Aβ clearance through the BBB is affected in AD and whether this dynamic is affected by an impaired peripheral clearance due to other non-neurological pathological conditions. Nonalcoholic fatty liver disease (NAFLD), is a spectrum of liver disorders characterized by accumulation of fat in the liver accompanied by varying degrees of inflammation and hepatocyte injury. In the last decade, NAFLD has been the focus of intense research due of its pandemic reach (estimated prevalence between 20 and 30% of the general population). This review summarizes the current state of the literature linking NAFLD and Alzheimer ́s disease, highlighting the role of the major Aβ efflux and clearance player - the LRP1 receptor- which is abundantly expressed in liver, brain, and vasculatures.